Myanmar's rising buddhist nationalism : impact on foreign investors - Kyaw, Nyi Nyi (2014)
Amidst rising Buddhist nationalism in Myanmar, domestic tension is beginning to affect foreign investment. The call to shun Qatar-based Ooredoo’s telecommunication services in Myanmar displays economic nationalism that should worry risk analysts.